Laminar forced convection to a pseudoplastic fluid food in circular and annular ducts - Gratao, ACA; Silveira, V; Telis-Romero, J. (Elsevier B.V., 2006)
In this manuscript we investigated experimentally the steady-state heat transfer to an important pseudoplastic fluid food, the soursop juice, flowing in laminar regime through circular and concentric annular ducts. The mean convection heat transfer coefficients, determined by measuring the bulk temperatures before and after the heating sections with constant temperatures of the tube walls, were used to correlate simple new empiric expressions to estimate the average Nusselt number in the thermal entrance of the considered geometries. In addition, the thermophysical properties of the tested fluid food, as well as the rheological behavior, being essential for the heat transfer analyses, were experimentally determined. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: circular pipe; concentric annuli, laminar flow; forced convection; Nusselt number